Fault estimation and compensation for hypersonic flight vehicle via type-2 fuzzy technique and cuckoo search algorithm. (6th January 2020) - Wang, Ang; Gong, Huajun; Chen, Fuyang
This study proposes a fault estimation and compensation scheme for hypersonic flight vehicle (HFV) attitude system with body flap fault. To achieve the fault compensation capability, an interval type-2 fuzzy estimator is designed to approximate the unknown nonlinear function caused by modeling uncertainties and the fault. The fault-tolerant controller via the terminal sliding mode and dynamic surface techniques is developed to ensure the tracking accuracy of attitude angles for HFV and the desired control torque can be achieved. Then, a novel control allocation scheme with a cuckoo search algorithm and linear programming method is proposed to distribute the desired torque to aerodynamic surfaces and reaction control system jets. The stability of the proposed scheme is analyzed using the Lyapunov stability theory. The validity of the method is verified by a series of comparisons on numerical simulation results.